PENGARUH MODEL TWO STAY TWO STRAY DALAM PEMBELAJARAN TEKS TANGGAPAN SISWA KELAS VII SMP NEGERI 12 KOTA JAMBI - Syah Ramadhan, Alan; Harahap, Eddy Pahar; Yusra, Hilman (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: This study aims to examine the effect of the Two Stay Two Stray learning model in teaching response texts, particularly focusing on their structure. It uses a quantitative method with a Quasi-Experimental Design. The data were obtained through pretests and posttests conducted in class VII-6 at SMPN 12 Kota Jambi. The data were analyzed using normality tests (Kolmogorov-Smirnov and Shapiro-Wilk) and the Wilcoxon test with the help of IBM SPSS version 29. Data collection techniques included observation, tests, and documentation. The study employed non-parametric statistical tests to compare data before and after the treatment. The results showed a significant difference in students' ability to write response text structures, with an average pretest score of 54.82 and a posttest score of 84.48. This indicates that the Two Stay Two Stray model is effective in engaging students and increasing their motivation to learn. The hypothesis test using the t-test revealed a Sig. (2-tailed) value of 0.000. These findings are expected to serve as a reference for implementing multi-directional learning that emphasizes student understanding. Teachers, as facilitators, should adapt dynamically to the current learning environment, highlighting the effectiveness of the Two Stay Two Stray model in achieving educational goals.Keywords: Two Stay Two Stray, learning of response texts.